Theoretical prediction, synthesis, and crystal structure determination of new MAX phase compound V2SnC - Qiang Xu; Yanchun Zhou; Haiming Zhang; Anna Jiang; Quanzheng Tao; Jun Lu; Johanna Rosén; Yunhui Niu; Salvatore Grasso; Chunfeng Hu (Journal of Advanced Ceramics, 2020)
Abstract Guided by the theoretical prediction, a new MAX phase V2SnC was synthesized experimentally for the first time by reaction of V, Sn, and C mixtures at 1000 °C. The chemical composition and crystal structure of this new compound were identified by the cross-check combination of first-principles calculations, X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDS), and high resolution scanning transmission electron microscopy (HR-STEM). The stacking sequence of V2C and Sn layers results in a crystal structure of space group P63/mmc. The a- and c-lattice parameters, which were determined by the Rietveld analysis of powder XRD pattern, are 0.2981(0) nm and 1.3470(6) nm, respectively. The atomic positions are V at 4f (1/3, 2/3, 0.0776(5)), Sn at 2d (2/3, 1/3, 1/4), and C at 2a (0, 0, 0). A new set of XRD data of V2SnC was also obtained. Theoretical calculations suggest that this new compound is stable with negative formation energy and formation enthalpy, satisfied Born-Huang criteria of mechanical stability, and positive phonon branches over the Brillouin zone. It also has low shear deformation resistance c 44 (second-order elastic constant, c ij ) and shear modulus (G), positive Cauchy pressure, and low Pugh’s ratio (G/B = 0.500 < 0.571), which is regarded as a quasi-ductile MAX phase. The mechanism underpinning the quasi-ductility is associated with the presence of a metallic bond.